Evidence for and Against Subclinical Disease Activity and Progressive Disease in MOG Antibody Disease and Neuromyelitis Optica Spectrum Disorder. (5th December 2022) - Molazadeh, Negar; Filippatou, Angeliki G.; Vasileiou, Eleni S.; Levy, Michael; Sotirchos, Elias S.
Abstract : Objective: To investigate the evidence for and against relapse-independent clinical progression and/or subclinical disease activity in patients with Myelin Oligodendrocyte Glycoprotein Antibody Disease (MOGAD) and Aquaporin-4 IgG Seropositive Neuromyelitis Optica Spectrum Disorder (AQP4-IgG+ NMOSD). Background: MOGAD and AQP4-IgG+ NMOSD are generally relapsing disorders, without clinical progression or subclinical disease activity outside of relapses. With advances in the diagnosis and treatment of these conditions, prolonged periods of remission without relapses can be achieved, and the question of whether progressive disease courses can occur has re-emerged. Design/Methods: We conducted a narrative literature review in Ovid MEDLINE and Embase, exploring the evidence for and against relapse-independent progression in MOGAD and AQP4-IgG+ NMOSD. We classified the results in four categories : 1)Clinical observations, 2)MRI findings, 3)Retinal imaging, and 4)Fluid-based biomarkers. Results: As the optic nerve is the major site of involvement in MOGAD and AQP4-IgG+ NMOSD, much of the data comes from the visual pathway studies. Possible pathophysiologic mechanisms of the OCT abnormalities in the absence of symptomatic optic neuritis are: 1) primary neurodegenerative process in retina, 2) subclinical inflammation of the optic nerve, 3) chiasmal involvement leading to abnormal findings in the unaffected eye, and 4)trans-synaptic retrograde degeneration originating from inflammatory lesions in the posterior visual pathway. Except for chiasmal involvement, these mechanisms are not specific to the visual pathway, and are considered as potential explanations for subclinical disease activity outside of the retina. Outside of the visual pathway, there is a lack of sufficient evidence to support the existence of subclinical disease activity and/or relapse-independent clinical progression in MOGAD and AQP4-IgG+ NMOSD, although recent fluid-based biomarker data (serum NfL and GFAP) support that neuro-axonal and/or astrocytic damage may be ongoing between attacks in these diseases. Conclusions: This review highlights the many unknowns that remain in our understanding of the pathophysiology and clinical course of MOGAD and AQP4-IgG+ NMOSD.